INTERETHNIC HARMONY AND RELIGIOUS TOLERANCE ARE THE HIGHEST VALUES OF THE UZBEK PEOPLE - Botirova Gulsanam (International Engineering Journal For Research & Development, 2022)
When there is peace in any society, it rises and prospers. In particular, if there is inter-ethnic harmony and solidarity in the countries, a great future will be built. For the Uzbek people, interethnic harmony and religious tolerance are formed as values.